Analisis eksegetis 1 Kor. 13:4 mengenai makna kasih dalam frasa tidak memegahkan diri dan tidak sombong - Kariani Giawa; Aji Suseno (Sekolah Tinggi Alkitab Penyebaran Injil Majalengka, 2026)
This study presents an exegetical analysis of the phrases “does not boast” (περπερεύεται) and “is not arrogant” (φυσιόω) in 1 Corinthians 13:4. Through linguistic and contextual analysis, it distinguishes two dimensions of pride: perpereuetai denotes external, boastful behavior seeking public recognition, while physioō refers to an internal attitude of superiority. The findings reveal Paul’s intentional critique of self-centered spirituality in the honor-driven Corinthian community. Theologically, love (ἀγάπη) emerges as a transformative principle grounded in Christ’s humility. This study offers relevant insights for contemporary churches navigating digital-age tendencies toward self-promotion and spiritual narcissism.